Correction: Integrative species delimitation and five new species of lynx spiders (Araneae, Oxyopidae) in Taiwan. - Ying-Yuan Lo; Ren-Chung Cheng; Chung-Ping Lin (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0301776.].